Emotional Identification Using Autoethnography - Mars Caroline Wibowo; Budi Raharjo (University of Science and Computer Technology, 2023)
This study aims to explore the skills of emotion regulation and the use of visual expressions as nonverbal communication tools to raise awareness about the importance of identifying emotions and utilizing creativity and visual expression in dealing with emotions. Emotional intelligence has an important role in various fields, but attention to aspects of emphasizing emotional intelligence in communication design is still limited. Effective communication design must take into account the emotional impact on the audience, not just conveying information. The role of childhood adversity and generational trauma in shaping emotional regulation skills diminishes emotional intelligence in communication design. Research emphasizes the importance of emotional intelligence in communication design and explores the use of visual expressions as instruments of nonverbal communication. In addition, it is a valuable contribution to broadening the understanding of emotional intelligence and creative expression in effective communication. Autoethnography is employed as a strategy to delve into emotionally engaging design and to engage communities of individuals who may be uncertain or unskilled in effectively eliciting emotions from the written content. Through the process of autoethnography, the results of this study show personal progress in identifying emotions. This study creates awareness of the importance of emotional identification exercises and education about using ambient materials to deepen emotional experience through creativity and visual expression. Through an autoethnographic process, this study records personal progress in identifying emotions. Awareness of the importance of practicing emotional identification and utilizing surrounding materials to immerse oneself in emotional experiences, especially through creativity and visual expression, is also emphasized.